A giant neobladder stone with insignificant symptoms: A case report and literature review - Gu, Jun; He, Zexi; Li, Haihao; Liu, Yijie; Wang, Haifeng; Huang, Yinglong; Ding, Mingxia (Frontiers in Surgery, 2023)
Background Giant neobladder lithiasis after orthotopic bladder replacement is an infrequent but important long-term complication, which should be diagnosed and treated early. If left untreated, it may eventually lead to irreversible acute kidney injury and seriously affect the quality of life of patients. Here, we present a rare case of a patient who presented with a massive neobladder stone after radical cystectomy done with orthotopic neobladder construction, followed by a challenging stone extraction process. Case presentation A 70-year-old female patient presented with a massive neobladder stone 14 years after radical cystectomy done with orthotopic neobladder construction. A computed tomography scan showed a large elliptic stone. The patient underwent suprapubic cystolithotomy surgery, which removed her giant-sized stone in the neobladder. The size of the bladder stone that was removed was 13 cm × 11.5 cm × 9 cm, with a total weight of 903 g. To date, the follow-up time of treatment is 4 months, and in our patient, no pain, urinary tract infections, or other abnormalities suggestive of fistula were found. Conclusion Imaging examination is useful for detecting neobladder lithiasis occurring after orthotopic neobladder construction. Our experience demonstrates that open cystolithotomy is an appropriate therapeutic method for treating the late-stage complication of a giant neobladder stone.